Fatty acid requirements for the preterm infant. Issue 1 (February 2017) - Robinson, Daniel T.; Martin, Camilia R.
Summary: Fatty acids are critical nutrient regulators of intracellular signaling and influence key pathways including inflammatory responses, hemostasis as well as central nervous system development and function. Preterm birth interrupts the maternal–fetal transfer of essential fatty acids including docosahexaenoic and arachidonic acids, which occurs during the third trimester. Postnatal deficits of these nutrients accrue in preterm infants during the first week and they remain throughout the first months. Due to the regulatory roles of these fatty acids, such deficits contribute an increased risk of developing prematurity-related morbidities including impaired growth and neurodevelopment. The fatty acid contents of parenteral and enteral nutrition are insufficient to meet current recommendations. This chapter summarizes the regulatory roles of fatty acids, current recommendations and limitations of parenteral and enteral nutrition in meeting these recommendations in preterm infants. Suggested areas for research on the roles of fatty acids in preterm infant health are also provided.